Schema corporeo: tra Paul Schilder e Maurice Merleau-Ponty - LAMBERTI, FRANCESCO (S&F_scienzaefilosofia.it, 2023)
Body schema: between Paul Schilder and Maurice Merleau-Ponty This article aims to investigate the theme of body schema in Paul Schilder’s work, The Image and appearance of human body, and Merlau-Ponty’s writings of 1940s. The choice of dealing with this topic is motivated by the importance of the notion for the comprehension of the embodied existence, essential field of study in both science and philosophy. Therefore, starting with a brief introduction to the topic and emphasizing the importance of some crucial studies in the development of the concept, the article analyzes subsequently some significant aspects of Schilder’s conception: unity, synesthesia, movement, driving and emotional elements in the structuring of the image. The second part is mainly focused on Merleau-Ponty’s Phenomenology of perception, in order to show how the French philosopher surpasses a mere psychological conception of the schema to reach a phenomenological one.